Pemanfaatan Teknologi Digital dalam Pembelajaran SD: Analisis Kebijakan dan Tantangannya (Studi Kasus di SDN X Merangin) - Rega Rahayu; Rose Melia Serly; Herpinah Imel Eka Mulyani; Denia Putri Rizkia; Iskandar; M Ali Basroh; Anggia Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the utilization of digital technology in elementary school learning and analyze the supporting policies and challenges, specifically at SDN X Merangin. Digital technology utilization plays an essential role in enhancing learning quality, teacher-student interaction, and educational administration. This study employed a descriptive qualitative approach with four teachers and one principal as subjects. Data were collected through interviews, observation, and documentation, then analyzed thematically. The results indicate that digital technology has been applied to support both online and offline learning; however, its implementation is influenced by device availability, teacher capacity, and school policy support. Key challenges include limited internet access, resistance from some teachers to innovation, and lack of intensive training. Overall, digital technology utilization has the potential to improve learning effectiveness but requires adaptive policies and continuous teacher training.